Transformation towards a Warm and Competent Leadership - Martin-Naranjo, Sonsoles; Gonzalez , Reyes; Gasco, Jose; Llopis, Juan (Transformations In Business & Economics, 2025)
Competence and warmth, the two essential dimensions of social judgment postulated by the Stereotype Content Model (SCM), are considered to be features of leadership. A hypothesis is posed that warm and competent leaders generate more committed and loyal employees. To test our hypotheses, a cross-sectional study was performed, examining the shop workers (N = 792) of a low-cost fashion retailer. The results show that warmth has almost three times more influence on employee experience than competence. Beyond salary and other perks, employees need to feel valued by their organisations and leaders via significant interactions ―albeit not necessarily in person― and not only in terms of transactions. By failing to understand what their employees are fleeing from and how to connect with them, company leaders are putting their businesses at risk. Leaders must be humble and show interest in people; it is also necessary to implement strategies destined to develop employee talent.